A PILOT PROJECT TARGETING FREQUENT ATTENDERS AT THE EMERGENCY DEPARTMENT WITH MEDICALLY UNEXPLAINED SYMPTOMS. Issue 10 (7th September 2013) - Baker, M; Stallard, J; Gibson, S
Abstract : Objectives & Background: We identified that there is a cohort of people who attend our Emergency Department (ED) extremely frequently (>24 times per year) or who have frequent admissions (>12 per year). Analysing hospital clinical records identified that in many cases medically unexplained symptoms (MUS) drive the frequent presentation. The needs of these patients were not being met by a traditional dualistic approach in which people are seen in either physical or mental health settings. Indeed, despite frequent medical investigations/treatments, their symptoms persist, their problems are not resolved, they frequently complain and they keep coming back. This carries risk and distress for the patients, and heavy use of resources for the hospitals involved. Methods: Each month we looked at attendance data for the previous 3 months (this identified people who in an acute phase of repeat presentations). By accessing patients clinical records we determined the main factors which appeared to drive their frequent attendance and admissions and identified those who presented with MUS. Care plans were developed and each patient was contacted and offered weekly Cognitive Behavioural Therapy (CBT) sessions to help them manage their symptoms. This was part of a case management approach in which coordinated, multidisciplinary reviews were undertaken resulting in an individualised care plan. Results: Thus far the pilot has seen a reduction in attendances at ED for 100% of patients included in study (N=20). Crucially, all now attend less than once per month. In total 245 attends were saved after the CBT interventions Conclusion: Providing a psychological intervention to this patient cohort is effective in reducing hospital costs by containing the most frequent attenders. CBT and care plans have reduced attendance to under once per month and subsequently reduced medical interventions and prescribing costs.